(untitled) (Journal of Philosophy Culture and Political Science, 2019)
The article provides a new interpretation of the term “regulation of ethnic confl icts” based on the review of the Western theories and analyses its conceptual difference from other activities connected with the manipulation of the ethnic confl icts. Apart from this, the author provides an assessment of the recent trends in the international relations analyzing its impact on the formation of the meaning apparatus. Keywords: confl ict, ethnic confl ict, confl ict management, the international community